Pengaruh Pengangguran, Pengeluaran Pemerintah, Investasi Dan Inflasi Terhadap Pertumbuhan Ekonomi Di Indonesia Pada Tahun 1989-2019 - Fadhilla Ashari; Menik Kurnia Siwi (Universitas Negeri Padang, 2022)
The purpose of this research is to use multiple linear regression analytic techniques to examine the effects of unemployment, government expenditure, investment, and inflation on economic growth in Indonesia from 1989 to 2019. This research uses time series data for the period 1989-2019, with data collection obtained from the Central Statistics Agency (BPS), the Investment Coordinating Board (BKPM), and Bank Indonesia (BI), and spans the years 1989 to 2019. Unemployment (X1), Government Expenditure (X2), Investment (X3), and Inflation (X4) are the independent variables in this research, whereas Economic Growth (X4) is the dependent variable (Y). Ordinary Least Square (OLS) was utilized in this research, which includes a stationarity test, a classical assumption test, a coefficient of determination test (R2), and hypothesis testing with t-test and f-test at a significance level of 5%. The estimation results show that unemployment has a non-significant positive relationship with Indonesian economic growth, government expenditure has a significant positive effect on Indonesian economic growth, investment has a significant positive effect on Indonesian economic growth, and inflation has a significant negative effect on Indonesian economic growth. Unemployment, government expenditure, investment, and inflation all have a substantial impact on Indonesia's economic growth.